Biological attributes of lemon: A review - Sania Rafique; Syeda Mona Hassan; Shahzad Sharif Mughal; Syed Khurram Hassan; Nageena Shabbir; Sumaira Perveiz; Maryam Mushtaq; Muhammad Farman (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
The citrus fruits are originate to be frequently in cultivation throughout the tropics and are extremely nutritious and medicinal in nature. According to Ayurveda, different parts of Lemon tree possess various medicinal properties. Many properties such as anti-inflammatory, anti-viral, anti-oxidant and anti-diabetic are shown by lemon. In the present review important effects such as anti-fungal, anti-oxidant, anti-inflammatory, anticancer, antibacterial, anti-ulcer and desorption also have been studied In lemon, very important natural compounds containing ascorbic acid, minerals, citric acid, essential oils and flavonoids are present in high quantity9. lemon shows anticancer and antibacterial activity due to the presence of alkaloid constituent in different parts of lemon leaves, stem, root and flower. Millennium development goals (MDGs) have one of the fundamental goal which is the quest to combat the incidence of diseases such as kidney stone, respiratory disorder, cancer blood sugar balance and cardiovascular diseases. The potential sources of drugs are secondary metabolites due to their therapeutic importance. These secondary metabolites are rich in medicinal plants.